DYNAMIC RESPONSE OF HIGH-POWER ULTRASONIC SYSTEM BASED ON FINITE ELEMENT MODELING OF PIEZOELECTRIC - Luong, Viet Dung (Journal of Applied Engineering Science, 2023)
In this study, a new finite element model for ultrasonic welding equipment is proposed. This help to solve remaining issues such as element type selection for the numerical model, mesh size, and how to determine the parameters of piezoelectric materials. The obtained results clearly show the influence of element type and mesh size on resonance frequency and amplitude. Specifically, with a mesh size of 2 mm, it was concluded to be suitable for the model. For the C3D8 element (C3D8E), the computation time is reduced by 0.25 times compared to the C3D20R element (C3D20RE). After that, an experimental processing procedure is performed to evaluate the numerical simulation results. Specifically, the handling of signal noise when measuring a very small displacement at high frequencies of an ultrasonic vibrating device. Based on the confirmed finite element model, this model is extended to evaluate the influence of the load on the amplitude and resonant frequency of the ultrasonic welding system. The results show that when the load increases, the amplitude decreases while the resonant frequency increases. The results of this study can be applied to the design of ultrasonic vibration systems.
Keywords: finite element, ultrasonic transducer, resonance frequency, amplitude, vibration